Academic, Personal, Social and Vocational Needs of International and Exchange Students at the University of Puerto Rico, Río Piedras Campus - Ángel A Villafañe-Santiago; Carol Y Irizarry-Robles; Robinson A Vázquez-Ramos (Universidad Nacional, Costa Rica, 2011)
The purpose of this study was to identify the needs of a sample of the international and exchange students staying at the North Tower Residence of the University of Puerto Rico, Río Piedras Campus. Social and demographic data, as well as the academic, vocational, and social/personal needs were explored with the purpose of gathering relevant information and submitting recommendations to universities serving this student population. Findings revealed particular needs in the academic, vocational areas, including English or Spanish learning, information on internships and study programs in Puerto Rico or abroad, salary and employment opportunities, financial aid and services available to the students of this University. Recommendations are provided to work with the identified needs. According to the literature, difficulties faced by these students may affect their academic performance and emotional health.